Effectiveness of Augmented Reality (AR) Media Usage with the POGIL Learning Model in IPAS Learning at UPT SDN 212 Pinrang - Muliati Muliati; Masnur Masnur; Yunus Busa (Edumaspul: Jurnal Pendidikan, 2024)
Natural and Social Sciences learning requires innovative approaches that can integrate modern technology with effective learning methods. This research aims to analyze the effectiveness of using Augmented Reality media with Process Oriented Guided Inquiry Learning model in improving student learning outcomes in Natural and Social Sciences subjects at UPT SDN 212 Pinrang. The research method used a quasi-experimental design with pretest-posttest control group design involving 60 fifth-grade students divided into experimental and control groups. The experimental group used Augmented Reality media with Process Oriented Guided Inquiry Learning model, while the control group used conventional learning. Research instruments included learning outcome tests, student activity observation sheets, and learning motivation questionnaires. Data analysis techniques used descriptive and inferential statistics with independent sample t-test and paired sample t-test. The results showed significant improvement in the experimental group with pretest average of 68.7 increasing to 85.3 in posttest, while the control group increased from 67.9 to 74.2. Independent sample t-test showed significant differences between both groups with p-value < 0.05. Learning motivation analysis showed significant improvement with average score of 89.4 in the experimental group compared to 76.2 in the control group. The research conclusion indicates that using Augmented Reality media with Process Oriented Guided Inquiry Learning model is effective in improving learning outcomes and student motivation in Natural and Social Sciences learning. The integration of Augmented Reality technology with inquiry learning approach provides immersive and interactive learning experiences that enhance understanding of abstract concepts into more concrete ones.